2019
DOI: 10.1055/s-0039-1688978
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Neuropathy

Abstract: Diabetes mellitus is becoming increasingly common worldwide. As this occurs, there will be an increase in the prevalence of known comorbidities from this disorder of glucose metabolism. One of the most disabling adverse comorbidities is diabetic neuropathy. The most common neuropathic manifestation is distal symmetric polyneuropathy, which can lead to sensory disturbances, including diminished protective sense, making patients prone to foot injuries. However, focal, multifocal, and autonomic neuropathies are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 69 publications
(111 reference statements)
3
61
0
3
Order By: Relevance
“…Most of the samples had type 2 diabetes, women, pain duration up to 12 years, and a mean age of 59. This is consistent with the previous theory that DN is more common in older adults (> 50 years) because of the time it takes for nerve damage and pain to occur (Zakin, Abrams, & Simpson, 2019), with an increased risk for type 2 DM patients, women, the prevalence of DN increases, and 23.5% after seven years (Iqbal et al, 2018). This suggests the need for early fuses, DN pain symptoms, especially in type 2 DM, to prevent the risk of complications.…”
Section: Sample On the Studysupporting
confidence: 92%
“…Most of the samples had type 2 diabetes, women, pain duration up to 12 years, and a mean age of 59. This is consistent with the previous theory that DN is more common in older adults (> 50 years) because of the time it takes for nerve damage and pain to occur (Zakin, Abrams, & Simpson, 2019), with an increased risk for type 2 DM patients, women, the prevalence of DN increases, and 23.5% after seven years (Iqbal et al, 2018). This suggests the need for early fuses, DN pain symptoms, especially in type 2 DM, to prevent the risk of complications.…”
Section: Sample On the Studysupporting
confidence: 92%
“…Our study found that nerve invasion was associated with impaired fasting glucose and DM, which was consistent with previous studies. Diabetes can induce damage to peripheral nerves ( 22 ). Is the damage related to nerve invasion?…”
Section: Discussionmentioning
confidence: 99%
“…It is related to time of disease and poor glycemic control and has multifactorial pathogenesis. Early diagnosis is a key factor to manage this condition, and slowing its progression by modifying risk factors is the prevalent therapeutic approach (3).…”
mentioning
confidence: 99%